Challenges of adult users of hearing amplification during the Covid -19 pandemic - Nikolić, Mina; Ostojić Zeljković, Sanja; Jotić, Ana; Đoković, Sanja (Specijalna edukacija i rehabilitacija, 2023)
Challenges of adult users of hearing amplification during the Covid – 19 pandemic Mina A. Nikolića, Sanja B. Ostojić Zeljkovića, Ana D. Jotićb,c, Sanja T. Đokovića a University of Belgrade – Faculty of Special Education and Rehabilitation, Belgrade, Serbia b University Clinical Center Serbia, Clinic for ENT and MFH, Belgrade, Serbia c University of Belgrade – Faculty of Medicine, Belgrade, Serbia Introduction. The Covid-19 pandemic has considerably affected many aspects of human life, especially healthcare and social services. The contacts of elderly people with family and friends, as well as their social activities, have been drastically reduced due to fear of contagious diseases with potentially serious consequences. Preventive measures of physical distancing and obligatory protective masks have brought additional challenges for hearing-impaired persons because of the decreased intensity and muffled quality of speech signals as well as the lack of visual cues because of the face masks. Objective. The study aimed to identify the challenges that adult hearing aid users faced during the Covid-19 pandemic. Methods. A special questionnaire was developed for the purpose of this study with a 3-point Likert type of scale. Results. The results of the study have shown that effective communication with other people during the pandemic was a great challenge for hearing-impaired participants. They pointed out the use of face masks and avoidance of communication with other people due to the fear of misunderstanding others. The participants noticed some changes in listening with hearing aids as well as mood swings and compliance to hearing aids. Most of the participants were satisfied with the access to hearing aids, fitting, and repair services, but none of them had access to rehabilitation and advisory support. Conclusion. The Covid-19 pandemic revealed the need for developing a network for alternative methods and approaches in surdology to provide advisory and rehabilitation services for hearing-impaired people as well as technical support for hearing aid users. That would be the way to provide ongoing support for hearing aid users, not only in extreme situations, such as the pandemic, but to increase the accessibility of those services in everyday life for all users.